ACE2 Receptor Usage across Animal Species by SARS-CoV-2 Variants - Masato Hatta; Gloria P. Larson; Yasuko Hatta; Wei Wang; Nannan Jiang; Yu-Jin Jung; Li Wang; Xiaoyu Fan; Brenda M. Calderon; Gaston Bonenfant; Xudong Lin; Chenchen Feng; et al. (Emerging Infectious Diseases)
We analyzed the receptor-binding activity and infectivity of 6 representative SARS-CoV-2 lineages in cell lines expressing angiotensin-converting enzyme 2 proteins from 54 different animal species. All viruses demonstrated infectivity in a broad range of species. Susceptible animal species could serve as natural reservoirs or intermediate hosts for SARS-CoV-2.